Enhancing ductility of titanium matrix composites by multimodal α-grains. (September 2019) - Wang, Shuai; Huang, LuJun; Zhang, Rui; Liu, BaoXi; Cui, XiPing; Geng, Lin; Peng, Hua-Xin
Abstract: In order to improve the ductility of titanium matrix composites, laminated TiB/Ti-TiB/Ti-6Al-2Zr-1Mo-1 V composites was fabricated. Multimodal α-grains including columnar grains, recrystallized fine grains and near-equiaxed grains were formed during hot rolling process. Compared with the hot rolled monolithic TiB/Ti-6Al-2Zr-1Mo-1V composites, the uniform elongation of the multimodal grain structured composites was slightly improved (about 2% increase), and the non-uniform elongation was increased by 10% which is rather significant. While the slight uniform-elongation enhancement can be mainly attributed to columnar grains strain hardening and fine grains strengthening, it is the near-equiaxed grains that contributed most to the non-uniform elongation. Graphical abstract: Unlabelled Image